Layout improvements for just-in-time - Drozda, Thomas J.; Bollinger, Steven R. (Manufacturing insights, 1990)
This program tells benefits of layout improvements for JIT by eliminating wasted efforts. Case studies covers: TRW Steering & Suspension Division, Raytek, Calcomp.